2013
DOI: 10.1021/es304025x
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Reductive Immobilization of U(VI) by Biogenic Mackinawite

Abstract: During subsurface bioremediation of uranium-contaminated sites, indigenous metal and sulfate-reducing bacteria may utilize a variety of electron acceptors, including ferric iron and sulfate that could lead to the formation of various biogenic minerals in situ. Sulfides, as well as structural and adsorbed Fe(II) associated with biogenic Fe(II)-sulfide phases, can potentially catalyze abiotic U(VI) reduction via direct electron transfer processes. In the present work, the propensity of biogenic mackinawite (Fe 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 76 publications
8
76
0
Order By: Relevance
“…43,65 ■ DISCUSSION While limited reduction of U(VI) to U(IV) in the presence of mackinawite was observed in early work, 66 two recent studies have observed complete reduction of U(VI) to U(IV). 43,44 In agreement with these studies, we also observed 100% sorption of U(VI) to mackinawite followed by complete reduction of U(VI) to nano-UO 2 in the absence of As(V) (samples U47 and U470) after 48 h of reaction time (Table S5, Supporting Information). Previous studies observed uptake of U(VI) onto the mackinawite surface within 15 min at pH 7, while reduction of U(VI) followed uptake and occurred on a longer time scale of 4 h. 42 Although we did not conduct a time dependent study, U(VI) was fully reduced in samples without As(V) upon immediate mixing with mackinawite and filtration (Table S5, Supporting Information), suggesting immediate reduction of U(VI) and precipitation as the cause of removal from solution.…”
Section: Environmental Science and Technologysupporting
confidence: 87%
See 1 more Smart Citation
“…43,65 ■ DISCUSSION While limited reduction of U(VI) to U(IV) in the presence of mackinawite was observed in early work, 66 two recent studies have observed complete reduction of U(VI) to U(IV). 43,44 In agreement with these studies, we also observed 100% sorption of U(VI) to mackinawite followed by complete reduction of U(VI) to nano-UO 2 in the absence of As(V) (samples U47 and U470) after 48 h of reaction time (Table S5, Supporting Information). Previous studies observed uptake of U(VI) onto the mackinawite surface within 15 min at pH 7, while reduction of U(VI) followed uptake and occurred on a longer time scale of 4 h. 42 Although we did not conduct a time dependent study, U(VI) was fully reduced in samples without As(V) upon immediate mixing with mackinawite and filtration (Table S5, Supporting Information), suggesting immediate reduction of U(VI) and precipitation as the cause of removal from solution.…”
Section: Environmental Science and Technologysupporting
confidence: 87%
“…Hyun et al 43 and Veeramani et al 44 both suggested that U(VI) was reduced by structural S 2− rather than Fe(II), but the two studies proposed different oxidation products of S 2− , namely elemental sulfur and sulfate, respectively. Our results are most consistent with the mechanism proposed by Veeramani et al 44 because we Table 1. Summary of U L III -edge EXAFS Fitting Results for Selected U(VI) and As(V) Treatments 43 We measured a decrease in aqueous Fe(II) concentrations over the reaction period which rules out the possibility of exchange between Fe(II) and U(VI).…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Sediment sulfur concentrations (measured by Larson et al [4] ) and sediment Fe concentrations in the pond could allow for the precipitation of amorphous FeS, following microbial reduction of sulfate and Fe III oxy(hydr)oxides, which can abiotically reduce uranyl to uraninite or non-uraninite U IV . [4,13,15,27,65] Because of the low environmental sediment U concentrations, U XANES spectra were only obtained for the top of the tailings, toe of the tailings, pond and pond outlet (Figs S7, S8, Table S2 of the Supplementary material). Of the collected spectra, the U XANES spectrum from the pond outlet was fit with the greatest percentage of U IV (45.1 %).…”
Section: Geochemical Controls On U Transportmentioning
confidence: 99%
“…[22,23] Uranium can also be reduced by precipitated or biogenically produced Fe-sulfide and by aqueous sulfide under anoxic conditions. [15,[24][25][26][27] Enzymatic reduction of U VI has been observed by iron and sulfate reducing bacteria. [28,29] Although both As III and As V can be adsorbed to iron minerals, As can be released, not only by desorption, but by microbial reduction of iron mineral phases, resulting in mineral dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…One promising strategy for the remediation of uranium aims at transforming the soluble and mobile hexavalent form of uranium, U(VI), to the reduced and relatively immobile tetravalent form, U(IV) (O'Loughlin et al, 2003;Jeon et al, 2005;Wall and Krumholz, 2006;Burgos et al, 2008;Sheng et al, 2011;Zhang et al, 2011 reduction of U(VI) to U(IV) was only found to produce the sparingly soluble mineral uraninite, UO 2(s) (Lovley et al, 1991;Lovley and Phillips, 1992;Lovley, 1993;Burns, 1999;O'Loughlin et al, 2003;Wall and Krumholz, 2006;Burgos et al, 2008). However, recent research reveals that non-uraninite species of U(IV), i.e., those lacking the 3.85 Å U-U pair correlation characteristic of UO 2 observed using X-ray absorption spectroscopy (XAS), can form as the product of U(VI) reduction by Gram-negative and Gram-positive bacteria (Bernier-Latmani et al, 2010;Fletcher et al, 2010;Boyanov et al, 2011;Cologgi et al, 2011;Ray et al, 2011;Sivaswamy et al, 2011), by biogenic Fe(II)-bearing minerals (Veeramani et al, , 2013Latta et al, 2012), and in biostimulated or naturally reduced sediments (Campbell et al, 2011;Sharp et al, 2011). It is unknown if these U(IV) species occurs as amorphous solids or coordination polymers, as complexes sorbed to biomass functional groups, or as a mixture of the above.…”
Section: Introductionmentioning
confidence: 99%